Natural Vaccine Adjuvants and Immunopotentiators Derived From Plants, Fungi, Marine Organisms, and Insects - Woods, N.; Niwasabutra, K.; Acevedo, R.; Igoli, J.; Altwaijry, N.A.; Tusiimire, J.; Gray, A.I.; Watson, D.G.; Ferro, V.A. (In Immunopotentiators in Modern Vaccines, 2017)
Secondary metabolites from natural sources have made a significant contribution to medicine for millennia. In modern medicine, drugs developed from natural products have been used to treat infectious diseases, cancer, hypertension, and inflammation. Research on immunomodulators for application in vaccines has been sporadic, but it stands to reason that the field could better exploit the biodiversity of active compounds from natural sources.
Keywords: Natural vaccine adjuvants; Immunopotentiators; Plants; Fungi; Marine Organisms; Insects